2022
DOI: 10.3390/su142013053
|View full text |Cite
|
Sign up to set email alerts
|

Board Group Faultlines, Slack Resource, and Corporate Carbon Performance

Abstract: A general consensus has been reached among many countries that low-carbon development is important for the protection of the environment and the mitigation of climate change. In line with the attitude of a responsible country, China urges enterprises to participate in energy conservation and emission reduction through various policies. Based on the faultline theory, this paper considers the data of 124 listed companies in China’s manufacturing industry from 2015 to 2019 as a research sample. From the perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Finally, businesses can enhance sustainable marketing through promotion and advertising, increasing consumer awareness and trust in low-carbon buildings, thereby improving brand competitiveness and market share. In conclusion, promoting low-carbon buildings holds important theoretical and practical significance [58]. Governments and businesses should work together to promote the development and adoption of low-carbon buildings, driving the construction of a more environmentally friendly, energy-efficient, and sustainable society in China.…”
Section: Research Significancementioning
confidence: 99%
“…Finally, businesses can enhance sustainable marketing through promotion and advertising, increasing consumer awareness and trust in low-carbon buildings, thereby improving brand competitiveness and market share. In conclusion, promoting low-carbon buildings holds important theoretical and practical significance [58]. Governments and businesses should work together to promote the development and adoption of low-carbon buildings, driving the construction of a more environmentally friendly, energy-efficient, and sustainable society in China.…”
Section: Research Significancementioning
confidence: 99%
“…Pollution and emissions reduction are both an enterprise's social liabilities and its need for survival and development. Improving carbon performance is conducive to the long-term sustainable development of enterprises [ 10 ]. Researchers have found that carbon performance can have an intertemporal impact on an enterprise's financial performance and considerably enhance it 8.…”
Section: Introductionmentioning
confidence: 99%